Analysis of Main Components Status of Food Security at Village/Sub-District Level in Yogyakarta Special Region - Parwodiwiyono Suparna (Jurnal Matematika MANTIK, 2020)
Food is a basic aspect of the needs of human life to ensure the survival of individuals and communities. The realization of national food security starts from the fulfillment of food in the smallest region, namely the village /sub-districts. The objectives of the analysis using the principal component method are (1) to describe the main components of the status of food security at the village/sub-districts level; (2) to grouping villages/sub-districts based on food security status in the Yogyakarta Special Region. The data source of analysis comes from secondary data (Podes 2018). From the analysis produced several things, namely: (1) the main components of the status of food security at the village/sub-district level in the Yogyakarta Special Region there are five, namely affordability/access, food availability, environmental health, guaranteed access, and utilization of food; (2) village/sub-districts typology based on the status of food security in the Yogyakarta Special Region, namely 4: (a) food insecurity covering 55 villages/sub-districts (b) less resistant to 169 villages/sub-districts; (c) typologies 3 are vulnerable to cover 170 villages/sub-districts; (d) food-resistant typology covering 44 villages/sub-districts.